Amalgamation of N-graphene quantum dots with nanocubic like TiO2: An insight study of sunlight sensitive photocatalysis - Lim, Ping Feng; Leong, Kah Hon; Sim, Lan Ching; Azrina, Abd Aziz; Saravanan, Pichiah (Springer, 2019)
In this work, a sunlight-sensitive photocatalyst of nanocubic-like titanium dioxide (TiO2) and N-doped graphene quantum dots (N-GQDs) is developed through a simple hydrothermal and physical mixing method. The successful amalgamation composite photocatalyst characteristics were comprehensively scrutinized through various physical and chemical analyses. A complete removal of bisphenol A (BPA) is attained by a synthesized composite after 30 min of sunlight irradiation as compared to pure TiO2. This clearly proved the unique contribution of N-GQDs that enhanced the ability of light harvesting especially under visible light and near-infrared region. This superior characteristic enables it to maximize the absorbance in the entire solar spectrum. However, the increase of N-GQDs weight percentage has created massive oxygen vacancies that suppress the generation of active radicals. This resulted in a longer duration for a complete removal of BPA as compared to lower weight percentage of N-GQDs. Hence, this finding can offer a new insight in developing effective sunlight-sensitive photocatalysts for various complex organic pollutants degradation.